Money, banking and monetary policy - Kreps, Clifton H.; Pugh, Olin S. (New York, Ronald Press Co., 1967)
This edition presents a highly integrated exposition of the essential principles of money and banking. Major emphasis is placed on monetary policy and on those matters directly relevant to the student's understanding of the formation, execution, and economic usefulness of policy. This second edition reflects two major approaches which have recently developed in the teaching of money and banking. The first approach is to give increased and more intensive attention to the development and current content of monetary theory. The second approach, underlined by increasingly severe American balance-of-payments difficulties since the late 1950's, is to stress analysis of the causes of, and cures for, these difficulties.
Includes bibliographies.
rpm 24/04/2018
Loans
Keywords: Money; Banks and banking; Currency question; Monetary policy